Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan dan Sikap Ibu dalam Pemberian ASI Ekslusif di Wilayah Kerja UPT Puskesmas Marina Permai Kota Palangka Raya Tahun 2022: The Effect of Health Education on Knowledge and Attitude in Exclusive Breastfeeding at the Marina Permai Public Health Center Palangka Raya City Year 2022 - Elis Anjelina; Rizki Muji Lestari; Dita Wasthu Prasida (Jurnal Surya Medika (JSM), 2023)
Exclusive breast milk (ASI) is the first and foremost food for babies from 0-6 months of age, in fact there are still many mothers who choose to give formula milk with the assumption that formula milk is better than exclusive breastfeeding. Lack of knowledge from the community and support from families that the benefits of exclusive breastfeeding are very important for babies. To anticipate this, it is necessary to provide health education to increase knowledge and attitudes of mothers. The purpose of this study was to determine the effect of health education on knowledge and attitudes of mothers in exclusive breastfeeding. The design of this study uses an experimental with a one-group pre-posttest design. The population in this study were all breastfeeding mothers, with a total sample of 42 respondents. The sampling method used is purposive sampling. Data for this study were collected twice, once before and once after the intervention, using a questionnaire. The existing data were tabulated and then analyzed using the Mc nemar test analysis test and marginal homogeneity. The results showed that there was an effect of health education on knowledge (p 0.000 a 0.05) and attitudes (p 0.001 a 0.05) of mothers in exclusive breastfeeding. For the puskesmas, they should increase socialization and outreach to the community, especially for mothers to breastfeed their babies immediately after giving birth for 6 months or to give exclusive breastfeeding without other additional food for 6 months.